In Vitro Evaluation of the Effect of Different Laser Irradiations on the Enamel Surfaces of Teeth Treated with Home Bleach Procedure - Bassir, Mahshid Mohammadi; Rezvani, Mohammad Bagher; Chiniforush, Nasim; Moradi, Zohreh (Journal of Lasers in Medical Sciences, 2013)
Introduction:The aim of this study was to evaluate the effect of dental surface treatment with Erbium-Doped Yttrium Aluminum Garnet(Er: YAG), Neodymium-Doped Yttrium Aluminium Garnet(Nd: YAG) and Carbon Dioxide Laser (CO2) lasers and sodium ascorbate to recently home bleached enamel by scanning electron microscope (SEM). Methods: Thirty extracted human third molars were selected for this in vitro study. The teeth were randomly divided in two groups including home bleached group and control group (non-bleached). In group 1, the samples were bleached by home bleach technique. No bleaching procedure was done in second the group which served as control group. Then, the samples of two groups were divided to five subgroups as follow: Subgroup 1: treated using Nd:YAG laser with output power of 1 W, Subgroup 2: treated using Er:YAG laser with output power of 0.5 W, Subgroup 3: treated using CO2 laser with output power of 0.5 W, Subgroup 4: sodium ascorbate 10%, Subgroup 5: no treatment. After treatments, the surfaces were evaluated using Scanning Electron Microscope (SEM) analysis. Results:The surfaces treated by Nd:YAG laser showed some melting and recrystallized areas and in some area droplet pattern was observed. But the surface treated by Er:YAG laser showed irregular and micro porous surface with flake pattern. CO2 laser treatment of home-bleached surfaces resulted in melting area and cracks. Sodium ascorbate did not change the home-bleached surface. Conclusion:Among different surface treatments used in this study, it seems that Er:YAG laser can best interact with home-bleached teeth.